Efavirenz Pharmacokinetics and Human Immunodeficiency Virus Type 1 (HIV-1) Viral Suppression Among Patients Receiving Tuberculosis Treatment Containing Daily High-Dose Rifapentine . (16th December 2021) - Podany, Anthony T; Pham, Michelle; Sizemore, Erin; Martinson, Neil; Samaneka, Wadzanai; Mohapi, Lerato; Badal-Faesen, Sharlaa; Dawson, Rod; Johnson, John L; Mayanja, Harriet; Lalloo, Umesh; Whitworth, William C; et al.
Abstract: Background: A 4-month regimen containing rifapentine and moxifloxacin has noninferior efficacy compared to the standard 6-month regimen for drug-sensitive tuberculosis. We evaluated the effect of regimens containing daily, high-dose rifapentine on efavirenz pharmacokinetics and viral suppression in patients with human immunodeficiency virus (HIV)-associated tuberculosis (TB). Methods: In the context of a Phase 3 randomized controlled trial, HIV-positive individuals already virally suppressed on efavirenz--containing antiretroviral therapy (ART) (EFV1), or newly initiating efavirenz (EFV2) received TB treatment containing rifapentine (1200 mg), isoniazid, pyrazinamide, and either ethambutol or moxifloxacin. Mid-interval efavirenz concentrations were measured (a) during ART and TB cotreatment (Weeks 4, 8, 12, and 17, different by EFV group) and (b) when ART was taken alone (pre- or post-TB treatment, Weeks 0 and 22). Apparent oral clearance (CL/F) was estimated and compared. Target mid-interval efavirenz concentrations were > 1 mg/L. Co-treatment was considered acceptable if > 80% of participants had mid-interval efavirenz concentrations meeting this target. Results: EFV1 and EFV2 included 70 and 41 evaluable participants, respectively. The geometric mean ratio comparing efavirenz CL/F with vs without TB drugs was 0.79 (90% confidence interval [CI] .72–.85) in EFV1 and 0.84 [90% CI .69–.97] in EFV2. The percent of participants with mid-interval efavirenz concentrations > 1mg/L in EFV1 at Weeks 0, 4, 8, and 17 was 96%, 96%, 88%, and 89%, respectively. In EFV2, at approximately 4 and 8 weeks post efavirenz initiation, the value was 98%. Conclusions: TB treatment containing high-dose daily rifapentine modestly decreased (rather than increased) efavirenz clearance and therapeutic targets were met supporting the use of efavirenz with these regimens, without dose adjustment. Clinical Trials Registration: NCT 02410772. Abstract : The use of rifamycin antibiotics is often complicated by clinically relevant drug-drug interactions. We characterized the modest impact of rifapentine-based tuberculosis (TB) treatment on the pharmacokinetics and human immunodeficiency virus type 1 (HIV-1) viral suppression of efavirenz-based antiretroviral therapy.